Comparison of the application of high pressure and pulsed electric fields technologies on the selective inactivation of endogenous enzymes in tomato products. (December 2016) - Andreou, Varvara; Dimopoulos, George; Katsaros, George; Taoukis, Petros
Abstract: Application of novel technologies such as high pressure (HP) or pulsed electric fields (PEF) on the remaining activity of endogenous tomato pectinolytic enzymes such as Pectinmethylesterase (PME) and Polygalacturonase (PG), responsible for tomato products texture was studied. HP combined with temperature (200–800 MPa @ 55–75 °C), PEF (5.5–12.5 kV/cm, 0–12 ms treatment time) and thermally treated (55–75 °C) samples were studied. After thermal treatment, PG appeared to be more resistant than PME. Opposite behavior was observed for HP treated samples. For PME inactivation more intense P-T process conditions were necessary compared to PG. For PEF treatment, 98% inactivation was observed at 12.5 kV/cm and 6 ms for PME, and at 5.5 kV/cm and 11 ms for PG. PME appeared to be more HP and PEF resistant compared to PG. The results support the potential application of HP and PEF to selectively inactivate PG while partially retaining PME in tomato juices, aiming in improved tomato products' textural characteristics. Industrial relevance: The aim of the tomato industry is to produce tomato products of desired textural and sensorial characteristics while increasing the yield by decreasing the evaporated water. This can be achieved by applying novel technologies such as high pressure (HP) processing or pulsed electric fields (PEF) that affect the remaining activity of the endogenous pectinolytic enzymes such as Pectinmethylesterase (PME) and Polygalacturonase (PG), responsible for the final texture leading to products with improved quality characteristics such as viscosity, color and consistency. However, HP treatment is a batch process and makes it difficult for the treatment of large quantities (production of small quantities of superior products could be the target of the application of HP technology), while PEF technology could be applied in line with the typical production flow of that kind of products before the cold break step. Highlights: Thermal, HP and PEF inactivation of tomato endogenous enzymes is studied. HP and PEF allow for selective inactivation of the two enzymes. Retention of PME and inactivation of PG for production of concentrated tomato products with increased yield